Re-examination of 1- vs. 3-Sets of Resistance Exercise for Pre-spaceflight Muscle Conditioning: A Systematic Review and Meta-Analysis - Ralston, Grant W.; Kilgore, Lon; Wyatt, Frank B.; Dutheil, Frédéric; Jaekel, Patrick; Buchan, Duncan S.; Baker, Julien S. (Frontiers in Physiology, 2019)
Recommendations on resistance training (RT) set-volume protocols in preparation for spaceflight muscular strength remains equivocal. A meta-analysis was performed on the effects of single-set (S), or three-set (M3) RT on muscular strength per exercise for different body segments (upper and lower body) and joint types. Computerised searches were performed on PubMed, MEDLINE and SPORTDiscusTM. Twelve studies were considered appropriate according to pre-set eligibility criteria. Outcomes analysed were pre-to-post muscular strength change on; multi-joint and single-joint combined; upper body only; lower body only; multi-joint exercises only; single-joint exercises only. Upper body exercise analysis on combined subjects and untrained subjects only reported greater but not significant strength gains with M3 (ES 0.37; 95% CI 0.09 – 0.82; P = 0.11 and ES 0.35; 95% CI -0.49 – 1.19; P = 0.42). Trained only subjects reported superior strength gains with M3 (ES 0.63; 95% CI 0.34 – 0.92; P = <0.0001). Lower body exercise on combined subjects and untrained subjects only reported superior strength gains with M3 (ES 0.35; 95% CI 0.10 – 0.60; P = 0.006 and ES 0.49; 95% CI 0.14 – 0.83; P = 0.005). Trained subjects only observed greater but not significant strength gains with M3 (ES 0.18; 95% CI -0.23 – 0.58; P = 0.39). Multi-joint exercise on combined subjects reported greater strength gains with M3 (ES 0.83; 95% CI 0.14 – 1.51; P = 0.02). Trained only subjects reported greater strength gains with M3 (ES 0.52; 95% CI 0.10 – 0.94; P = 0.02). Single-joint exercise on combined subjects and untrained only observed greater strength gains for M3 (ES 0.49; 95% CI 0.26 – 0.72; P = <0.0001 and ES 0.56; 95% CI 0.21 – 0.91; P = 0.002). Trained only subjects reported greater but not significant strength gains with M3 (ES 0.37; 95% CI -0.01 – 0.75; P = 0.06). For astronauts in space-flight preparation, the findings suggest that M3 training appears to be preferable over S for developing muscular strength. Nevertheless, depending on the physical conditioning of the crew member or tight pre-flight scheduling, S is still able to provide a positive strength training stimulus.